EnvironMentors: a mixed methods study of underrepresented youth pursuing environmentally focused STEM career paths - Nedland, Brock, author; Bruyere, Brett, advisor; Teel, Tara, committee member; Banning, James, committee member (Colorado State University. Libraries, 2012)
This thesis presents two manuscripts and addresses ways in which the EnvironMentors national organization can improve in its mission to increase the numbers of underrepresented youth entering environmentally-focused science, technology, engineering, and mathematics (STEM) fields. This mixed methods study focused on specific aspects of the program including finding predictors to aid in recruiting efforts and discovering key aspects of participant's experiences that can assist in reaching the desired outcome of increasing the success of EnvironMentors' programming. Both manuscripts were guided by past research and theoretical framework. In the first paper, a regression analysis was conducted predicting/to predict student participants' interest in studying about the environment in college using three criteria: (1) enjoy nature (2) awareness of environmental issues, and (3) interest in studying science, technology, and engineering (STE) in college. Results from this research indicated that enjoy nature and interest in STE orientations can predict students' interest in studying about the environment in college. The second manuscript is a case study and comparison of two EnvironMentors chapters with similar programmatic activities and whose participants share similar demographics. Focus groups, and mid program evaluations were used and analyzed. A deductive analysis approach was utilized to look for the presence of pre-specified categories in the data. Results indicated that students from both chapters place emphasis on expectations, challenges and issues, interactions, and motivation that they experience in their mentor relationships.
Keywords: EnvironMentors; youth; underrepresented; STEM